Adolescent girls’ perceived readiness for sex in Central Uganda - liminal transitions and implications for sexual and reproductive health interventions - Kyegombe, Nambusi; Buller, Ana Maria; Meiksin, Rebecca; Wamoyi, Joyce; Muhumuza, Richard; Heise, Lori (Taylor & Francis, 2022)
Young women in Uganda are at risk of negative sexual and reproductive health outcomes, in part because of sex with older men. Theoretically grounded in the concept of liminality, this paper examines perceived markers of adolescent girls’ suitability for sexual activity. In 2014, we conducted 19 focus group discussions and 44 in-depth interviews in two communities in Uganda. Interviews were conducted using a semi-structured tool, audiorecorded and transcribed verbatim. Interviews examined markers of transition between childhood, adolescence and adulthood and how these were seen as relating to girls’ perceived readiness for sex. Analysis was thematic. Pre-liminal status was most often accorded to childhood. Sex with a child was strongly condemned. Physical changes during puberty and children’s increasing responsibility, autonomy and awakening sexuality reflected a liminal stage during which girls and young women were not necessarily seen as children and were increasingly described as suitable for sex. Being over 18, leaving home, and occupying ‘adult’ spaces reflected post-liminal status and perceived appropriateness for sexual activity including for girls under the age of 18. Interventions that seek to prevent early sexual debut and sexual activity with older men have the potential to reduce sexual and reproductive health risks.
Keywords: Childhood; adolescence; adulthood; liminal transitions; readiness for sex; Uganda